Family Members Dealing With Childhood Cancer: A Study on the Role of Family Functioning and Cancer Appraisal - Van Schoors, Marieke; De Paepe, Annick Lena; Norga, Koenraad; Cosyns, Veerle; Morren, Hanne; Vercruysse, Trui; Goubert, Liesbet; Verhofstadt, Lesley Liliane (Frontiers in Psychology, 2019)
Objectives Childhood cancer is a life-threatening disease that poses significant challenges to the life of the diagnosed child and his/her family members. Based on the ABCX-model, the aim of the current study was to explore the association between family functioning, cancer appraisal and the individual adjustment of patients, parents and siblings. Methods Participants were 60 children with leukemia or non-Hodgkin lymphoma, 172 parents and 78 siblings (115 families). Time since diagnosis varied from zero to 33 months. Patients, parents and siblings completed the Family Environment Scale (FES), Perceived Stress Scale, Situation-Specific Emotional Reactions Questionnaire and Pediatric Quality of Life Inventory/Maudsley Marital Questionnaire. Results Family functioning and the appraisal of the cancer diagnosis proved to be related to patients’, parents’ and siblings’ cancer-related emotions and quality of life post-diagnosis. In addition, family members differed in their perception of some family functioning domains, the appraisal of the cancer diagnosis, positive feelings and quality of life. Discussion Our findings led to the conclusion that family functioning and the appraisal of the cancer diagnosis are important for the individual adjustment of patients, parents and siblings when facing a diagnosis of cancer in the child. Differences across members within one family and differences between families speak to the need of screening all family members and intervening at the level of individual as well as the family unit.